LEVELS OF HYPOXIA INDUCIBLE FACTOR-1α (HIF-1α) AND INTERCELLULAR ADHESION MOLECULE-1 (ICAM-1) AFTER INTRAVITREAL BEVACIZUMAB IN PROLIFERATIVE DIABETIC RETINOPATHY - Ressa Yuneta; Tjahjono Darminto Gondhowiardjo; Rahayuningsih Dharma; Sri Widia A. Jusman; Joedo Prihartono; Andi Arus Victor (International Journal of Retina, 2019)
Purpose: to assess the levels of Hypoxia-inducible factor-1α (HIF-1α) and intercellular adhesion molecule-1 (ICAM-1) in vitreous of proliferative diabetic retinopathy patients which were given intravitreal bevacizumab (IVB), as well as its relation to the central macular thickness (CMT) measured prior to vitrectomy. Methods: thirty-two eyes were randomized into two groups, one that received an IVB injection at 1-2 weeks previtrectomy and the control group which did not receive any injection. Measurement of HIF-1α and ICAM-1 was conducted using enzyme-linked immunosorbent assay (ELISA). The CMT were measured at the initial visit, prior to vitrectomy, and at follow up time (2, 4, and 12 weeks postoperatively) using Stratus OCT. Results: The mean levels of HIF-1α vitreous (ng/mg protein) in the control group and IVB respectively 0.020 (0.006; 0.077) and 0.029 (0.016; 0.21). Vitreous levels of ICAM-1 (ng /mL) in control group and IVB group were 20.10 (3.41; 40.16) and 23.33 (0.63; 68.5). The mean levels of HIF-1α and ICAM-1 vitreous obtained did not differ significantly between the two groups. Conclusion: The levels of HIF-1α and ICAM-1 in PDR patients do not decrease after one injection of intravitreal Bevacizumab 1-2 weeks prior to vitrectomy. The concentration of vitreous HIF-1α and ICAM-1 are not directly related to the CMT.